Performance of pilot-scale constructed wetland for treating stormwater - Maidiana Othman,; Zuliziana Suif,; Nordila Ahmad,; Siti Khadijah Che Osmi,; Mohamad Nazrul Hafiz Mohd Nadzri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Water scarcity and storm water management are two major challenges that effect the ecosystem and urban environment. In hot and humid country such as Malaysia, wastewater reuse should be encouraging whenever it is safe and economically feasible. Constructed wetlands (CW) have been recognized as one of the environmentally friendly technologies and successfully used for treating a diverse range of wastewaters. Constructed wetland can also be suitable habitat for native wetland plants and associated fauna. In an urban setting such as a university campus, a constructed wetland can also be landscaped as an educational and attractive green space, providing service learning and teaching opportunities for campus and surround community members. This study examines the performance of pilot-scale constructed wetlands as a sustainable wastewater treatment in Universiti Pertahanan Nasional Malaysia (UPNM) campus for treating and reusing the stormwater in the mini-reservoir. The pilot-scale of constructed wetlands have been designed and constructed in the laboratory using native wetland plant, the Cat-tail Typha Angustifolia. The pilot-scale of CW with vertical subsurface flow (VSF) system was able to remove all parameters better than horizontal subsurface flow (HSF) system. The highest percentage of removal of all parameters was at hydraulic retention time (HRT) of 5 hours and percentage of removal increased with an increase in HRT. The percentage of removal for total suspended solid (TSS), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and Dissolved Oxygen (DO) approximately 84%, 71%, 68%, and 25%. Thus, the constructed wetland had the potential to increase the water quality level of stromwater in UPNM campus in order to support the sustainability and Green Campus environment campaign.